HUBUNGAN STIMULASI ORANG TUA DENGAN PERKEMBANGAN MOTORIK KASAR ANAK USIA 0-3 BULAN DI WILAYAH KERJA PUSKESMAS LOANO - Hidayah Taufiqurrohmah (Lembaga Riset Pengabdian Masyarakat dan Publikasi Ilmiah Institut Teknologi Bhakti Putra Bangsa Indonesia, 2019)
Background research : An important period of children growth and development is at a chilhood. In a children development a stimulus or useful stimulation is needed, so that the children’s potency would be develop.Research Purposes : To know about the relationship between parent stimulation and rough motoric development of children 0-3 month in Loano Research Methods :The research is using analytical survey with cross sectional approach. The sample was taken by an acydental sampling technique with questioner primary data. The sample are 60 sample. Meanwhile, the data was analyzed by Spearman Rank test.Research Result : The statistic test result of Spearman Rank was obtained a Rhoxy value 0,526 and the significance rtabel was at 5% with N=60 is 0,413. So, 0,526 > 0,413. While (p-value) 0,000 < 0,05.Conclusion : There is a relationship between parent stimulation and rough motoric development of children 0-3 month in Loano Community of Health Center.Suggestion : Parents have to monitoring their childrens motoric development according to their age by stimulation.